Cryptosporidium oocysts in Ghanaian AIDS patients with diarrhoea. - Adjei, A.; Lartey, M.; Adiku, T.K.; Rodrigues, O.; Renner, L.; Sifah, E.; Bosompem, K.M. (East African Medical Journal, 2003)
Background:Although Cryptosporidium spp.infections in acquired immunodeficiency syndrome patients (AIDS) with chronic diarrhoea have been reported in several African countries, there is no information regarding cryptosporidial diarrhoea in Ghanaian AIDS patients. Objective:To investigate the occurrence of C. parvumand other gastrointestinal parasitic agents in Ghanaian AIDS patients with chronic diarrhoea. Design:Prospective study of HIV/AIDS patients with diarrhoea over a nine month period. Setting:Korle-Bu Teaching Hospital and Korle-Bu Polyclinic Accra, Ghana. Results:Analysis of stool specimens from clinically diagnosed HIV/AIDS (n=2I; mean CD4 count was 288 cells per microliter, 95% confidence interval of 237 to 340 cells per microliter) and HIV-seronegative (n=27) patients revealed C. parvumin six (28.6%) of HIV/AIDS and 10 (37.0%) of the HIV-seronegative patients, respectively. Three other HIV/AIDS cases had other infections involving Strongyloides stercoralis 4.8% (l/21) and Salmonella spp . 9.5% (2/21). There was no concomitant association between C. parvumand any other parasites found. Also, no enterobacteria was found in the HIV-seronegative patients. Conclusion:This study demonstrates the prevalence of Cryptosporidiumsp. in both HIV/ AIDS and HIV-seronegative individuals in Ghana. However, there was no statistical association between cryptosporidiosis and HIV/AIDS (p>0.05).